Gait asymmetry during 400- to 1000-m high-intensity track running in relation to injury history - Gilgen-Ammann, R.; Taube, W.; Wyss, T. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To quantify gait asymmetry in well-trained runners with and without previous injuries during interval training sessions incorporating different distances. Methods: Twelve well-trained runners participated in 8 high-intensity interval-training sessions on a synthetic track over a 4-wk period. The training consisted of 10 × 400, 8 × 600, 7 × 800, and 6 × 1000-m running. Using an inertial measurement unit, the ground-contact time (GCT) of every step was recorded. To determine gait asymmetry, the GCTs between the left and right foot were compared. Results: Overall, gait asymmetry was 3.3% ± 1.4%, and over the course of a training session, the gait asymmetry did not change (F1,33 = 1.673, P = .205). The gait asymmetry of the athletes with a previous history of injury was significantly greater than that of the athletes without a previous injury. However, this injury-related enlarged asymmetry was detectable only at short (400 m), but not at longer, distances (600-1000 m). Conclusion: The gait asymmetry of well-trained athletes differed, depending on their history of injury and the running distance. To detect gait asymmetries, high-intensity runs over relatively short distances are recommended.